La grève dans les services publics en droit français - Frossard, Joseph (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
This paper describes the limitations on the constitutional right to strike that apply to public employees in France. While recognizing the right to strike for all salaried workers, whether employed in the private or public sector, the Preamble to the 1946 Constitution, incorporated by reference into the present Constitution, allows for limitations being imposed on that right by statute. Indeed, specific legislation has either prohibited or limited the right to strike for various classes of public employees. This has been held constitutionally valid insofar as the statutory bar or restriction is required to prevent essential functions of the State from being interrupted or to ensure that the vital needs of the country are being provided for. Even where no specific restrictive legislation applies, strikes by the staff of « public services » — including not only central and local government employees, but also employees of major nationalized industries, institutions such as hospitals, and even private undertakings providing some public utility or service — are subject, under the Labour Code, to a number of restrictions. In particular, five days' notice of the strike must be given by a representative union. And certains forms of striking, such as rotating strikes, are prohibited. In addition, the employer authority may, under the doctrine of « essential services », make administrative regulations identifying which units or staff positions are considered essential. These regulations are subject to review by the administrative courts on the basis that the constitutional right to strike may only be curtailed insofar as is needed to preserve State authority and security or the safety of the public.